Preparation and Electrical Characterization of Poly(Aniline) NanoClay Composites - Ahlatcioglu, Esma; Senkal, Bahire Filiz; Okutan, Mustafa (WALTER DE GRUYTER GMBH, 2015)
In this work, synthesis and characterization of composite materials based on NanoClay(NC) and boric acid doped PolyAniline (PANI) is studied. PANI was successfully incorporated into NC to form PANI-NC composites. The resulting organic-inorganic hybrid material, PANI-NC was characterized by various physicochemical techniques. Formation of PANI inside the clay tactoid has been confirmed by X-ray diffraction studies (XRD), scanning electron microscope (SEM) and FT-IR. Also, conductivity and physical properties of the PANI-NC composites were investigated.
Keywords: NanoClay; PANI; conducting polymer; impedance properties; FILM-COATED ELECTRODE; POLYANILINE; NANOCOMPOSITES; SILICA; Materials Science